Circular Complementary Split Ring Resonator Rotation for Linear Array Millimeter Wave Microstrip Patch Antenna (ELEKTRIKA- Journal of Electrical Engineering, 2021)
This paper proposes multiple linear array millimeter wave MPAs that could operate at various frequencies depending on the angular rotation of the CSRR structure. The main contribution of this work is the range of frequencies of the linear array MPA found when the position of the CSRR structure is changed angularly. This is achieved by positioning the CSRR structure on the ground plane of the MPA and rotate it to an incremental of 22.5°. Computer Simulation Technology software is used to simulate the antenna designs. The performance of the antenna is evaluated against the single element millimeter wave MPA with similar angular rotation to the CSRR structure. The reflection coefficient graph shows at 0° rotation, the antenna has dual band performance at 26 GHz and 28 GHz. At 22.5° and 45° CSRR structure rotation, the antenna shows triple band performance with different operational frequencies and different polarization depending on the frequencies. Finally, at 67.5° CSRR structure rotation, the antenna now is operational only at 20 GHz frequency with horizontal polarization performance. Plus, the results between the single element MPA with circular CSSRR and the linear array MPA with circular CSRR shows similar behavior in which the rotation of the CSRR did not affect the antenna differently even with an increase of the number of elements. The millimeter wave MPA with CSRR angular rotation can be utilized in various applications as it covers multiple frequencies depending on the angle of rotation of the CSRR structure.
Keywords: CSRR, CST simulation, linear array MPA, millimeter wave frequency